PENGEMBANGAN LKS BIOLOGI BERBASIS PENDIDIKAN ABAD 21 TERINTEGRASI KEARIFAN LOKAL MBOJO PADA SISWA SMA - Muhammad Irwansyah; Ferawati Ferawati; Erni Suryani (Jurnal Biotek, 2019)
Teacher is highly considered influence on the education process. In the future the teacher must be able to compile learning tools and carry out learning strategies that can improve the skills of 21st century of the students. This research is a development research (research & development) which consists of 4 stages, namely defining, designing, developing and distributing. The aim is to find out the validity, practicality and effectiveness of biology LKS based on 21st century learning that integrated with local wisdom of mbojo in high school students. The research subjects were students of class XI  of SMAN 2 Kota Bima, 2018/2019. The Instruments used to collect data were validation sheets, observation sheets, and cognitive tests. The results of this study indicate that 21st century biology LKS integrated with local wisdom of mbojo meet valid criteria with a value of 3.31, practical with a value of 3.45 and effective with the percentage of student learning achievement of 83.33%.